Marketing (СО) электронный курс - Селевич, Т. С. экономист доцент Томского политехнического университета, кандидат экономических наук 1980- (TPU Moodle, 2016)
The course focuses on the research competencies' development for the commercial activity of the enterprise with the use of the English language. Students deepen knowledge of the marketing theory, brings ever professional vocabulary, learn to use a practical marketing tools, as well as gain experience in analytical work, on the basis of the decision of business-cases of international and Russian companies.